Association between maternal exposure to per- and polyfluoroalkyl substances and serum markers of liver function during pregnancy in China: A mixture-based approach. (15th April 2023) - Liao, Qian; Tang, Peng; Fan, Haoran; Song, Yanye; Liang, Jun; Huang, Huishen; Pan, Dongxiang; Mo, Meile; LeiLei,; Lin, Mengrui; Chen, Jiehua; Wei, Huanni; et al.
Abstract: Previous studies have shown that per- and polyfluoroalkyl substances (PFAS) may have hepatotoxic effects in animals. However, epidemiological evidence in humans, especially pregnant women, is limited. This study aimed to assess the association of single and multiple PFAS exposure with serum markers of liver function in pregnant women. A total of 420 pregnant women from the Guangxi Zhuang Birth Cohort were enrolled from June 2015 to April 2019. Nine PFAS were measured in the maternal serum in early pregnancy. Data for liver function biomarkers, namely, alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyltransferase (GGT), total bilirubin (TBIL), direct bilirubin (DBIL), and indirect bilirubin (IBIL), were obtained from medical records. In generalized linear model (GLM), there was a positive association of perfluorooctane sulfonate (PFOS) with ALT, perfluorodecanoic acid (PFDA) and perfluorobutanesulfonic acid (PFBS) with GGT, and perfluorohexane sulfonate (PFHxS) with TBIL and IBIL. In contrast, there was a negative association of perfluoroheptanoic acid (PFHpA) with TBIL. There were inverse U-shaped relationships of PFUnA with ALT and AST and PFDA with ALT by restricted cubic spline. The weighted quantile sum (WQS) regression model revealed the positive effects of the PFAS mixture on GGT, TBIL, DBIL, and IBIL. Bayesian kernel machine regression (BKMR) analysis confirmed that the PFAS mixture was positively associated with GGT, and PFBS was the main contributor. In addition, the BKMR model showed a positive association of individual PFBS with GGT, individual PFHxS with TBIL and IBIL, and a negative association of individual PFHpA with TBIL. Our findings provide evidence of an association between individual PFAS, PFAS mixture and maternal serum markers of liver function during pregnancy. Additionally, these findings also enhance concerns over PFAS exposure on maternal liver function and PFAS monitoring in pregnancy, reducing the effect of maternal liver dysfunction on maternal and infant health. Graphical abstract: Image 1 Highlights: Higher serum PFBS exposure is associated with higher GGT level. Higher serum PFHxS is associated with higher TBIL and IBIL levels. Higher serum PFHpA is associated with lower TBIL level. The relationships of PFUnA with ALT and AST, and PFDA with ALT and GGT are nonlinear. The joint effect of PFAS is positively associated with GGT, and PFBS is the main contributor.